1999
DOI: 10.1021/jo991201s
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Solid-Phase Syntheses of Conjugated Homooligomers and [AB] Alternating Block Cooligomers of Precise Length and Constitution

Abstract: A new iterative divergent/convergent solid-phase synthesis of precisely defined oligomers is described. The starting monomer is affixed to the solid support so that both ends are free for growth. The polymer-supported n-mer bearing alpha,omega-terminal iodides is divided into two portions. The smaller portion is converted to the polymer-supported (n + 2)-mer by coupling an alpha,omega-dialkyne to the two iodide ends. The larger portion is liberated from the polymer support and then coupled with the polymer-sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 30 publications
3
51
0
1
Order By: Relevance
“…The length of polymer wire can be controlled by the solid-phase reaction [19,20]. For example, it can be achieved by oxidized-coupling of a porphyrin, in which one side of its acetylene is fixed by a solid phase, to diethynylporphyrin, in which one side is free from TMS protection.…”
Section: Topography Of Porphyrin Wires On Various Surfacesmentioning
confidence: 99%
“…The length of polymer wire can be controlled by the solid-phase reaction [19,20]. For example, it can be achieved by oxidized-coupling of a porphyrin, in which one side of its acetylene is fixed by a solid phase, to diethynylporphyrin, in which one side is free from TMS protection.…”
Section: Topography Of Porphyrin Wires On Various Surfacesmentioning
confidence: 99%
“…[12] This method, when combined with solid-phase synthesis, furnished a block-alternating 23-mer consisting of oligo(1,4-phenylene ethynylene)s and oligo(2,5-thiophene ethynylene)s, the molecular length of which reached about 160 . [13] Conversely, oligo-and polythiophenes have been actively exploited for molecular devices, such as organic conductive materials, electroluminescence (EL) devices, organic lightemitting diodes (OLEDs), field-effect transistors (FETs), and so forth. [14][15][16][17] Roncali et al reported the synthesis and characterization of monodisperse soluble oligothienylenevinylenes with chain lengths up to 10 nm.…”
Section: Introductionmentioning
confidence: 99%
“…Combinatorial synthesis could be carried out in solution, but the simplicity of workout with immobilized substrates makes it the method of choice. Indeed, the solid phase synthesis has been used to synthesise conjugated molecules of precise length [70][71][72]. The low solubility of conducting polymers in most solvents makes them ideal to perform combinatorial chemistry reactions on the polymer.…”
Section: Combinatorial Coupling Of Diazonium Salts With Polyanilinementioning
confidence: 99%